Peran Financial Technology, Literasi Keuangan, dan Sikap Keuangan pada Kinerja UMKM Kota Batam - Ratna Veryani; Risca Azmiana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
the research investigates the influence of financial technology and financial activities on the business resilience of MSMEs in urban Batam. The study is motivated by the existing disparities in fintech adoption, financial literacy, and financial behavior among small business owners, which are critical determinants of organizational outcomes. Adopting a quantitative framework, a survey was conducted involving 187 local enterprises across the Batam Kota and Lubuk Baja districts. Primary data were collected via digital questionnaires and analyzed using a multiple linear regression model, facilitated by SPSS software. The empirical results domenstrate that financial technology, financial literacy, and financial attitudes exert a significant posititve impact on MSME performance, both individually (partially) and collectively (simultaneously). Specifically, financial technology emerged ad the most influential driver, followed by financial behavior and literacy. The coefficient of determination confirms that these three variables explain a substantial portion of the variance in business performance. Ultimately, this study validates that MSME growth is not the product of a single isolated factor but rather the result of a synergy between technological integration and robust financial competence. Consequentlu, strengthening both technological and financial dimensions is a vital strategy for ensuring the long-term sustainability and performance of the MSME sector.